Electromagnetic wave absorbing paint based on carbon fiber-molybdenum disulfide composite material, coating, preparation method and application
By using the electromagnetic wave absorption coating prepared by carbon fiber-molybdenum disulfide composite material, the existing materials have poor wave absorption effect and inconvenient use in the high-frequency band, and the effect of efficient electromagnetic wave absorption in the wide frequency band and suitable for complex surfaces is achieved.
Patent Information
- Application Number
- CN202411824855.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electromagnetic wave absorption materials have poor wave absorption effect in the high-frequency band, making it difficult to meet the requirements of high-frequency electromagnetic wave absorption such as modern radar and 5G. At the same time, traditional materials are mostly solid or powder form, which is inconvenient to use and difficult to apply to complex surfaces.
The electromagnetic wave absorption coating based on carbon fiber-molybdenum disulfide composite material is used to form a composite material with good impedance matching, lightweight and wide frequency wave absorption capability by combining the conductivity of carbon fiber and the dielectric and magnetic loss characteristics of molybdenum disulfide to achieve a multiple electromagnetic wave loss mechanism.
Excellent electromagnetic wave absorption performance is shown in the wide band 2 to 18GHz, especially in the high frequency band (above 10GHz), the electromagnetic wave absorption performance is significantly enhanced, the coating density is low, the adhesion is strong, and the durability is good. It is suitable for complex surfaces and reduces the preparation cost.
Smart Images

Figure CN119505676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to an electromagnetic wave absorbing paint and coating based on a carbon fiber-molybdenum disulfide composite material, and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern science and technology, electromagnetic waves are increasingly used in communications, radar, aerospace and other fields. However, the electromagnetic interference (EMI) problem that comes with it has gradually become prominent, posing challenges to the performance and safety of electronic equipment. In order to cope with these problems, the research and development of electromagnetic wave absorbing materials has become an important research direction.
[0003] At present, the common electromagnetic wave absorbing materials on the market are metal oxides, such as ferrite, cobalt oxide, etc. Metal oxide electromagnetic wave absorbing materials have good electromagnetic wave absorption effects in low frequency bands (such as 2-8 GHz), but the absorption effect decreases significantly in high frequency bands (>10 GHz), and it is difficult to meet the requirements of high-frequency electromagnetic wave absorption such as modern radar and 5G.
[0004] In addition, most of the current absorbing materials are in solid or powder form, which is inconvenient to use and difficult to apply to complex surfaces. Preparing absorbing materials into coatings and coating them on substrates can greatly broaden their application scope, especially in scenarios that require lightweight and flexibility, such as aerospace, stealth equipment, and wireless communications, which has important application value.
[0005] There are reports on graphene absorbing coatings in the prior art. Graphene has excellent conductivity and polarization effect, which makes it have good electromagnetic wave absorption potential. However, graphene is expensive, and its electromagnetic wave absorption ability is good in the low frequency band, but its performance in the high frequency band is obviously insufficient, which makes it difficult to meet the needs of modern high-frequency communications. Summary of the invention
[0006] In view of this, the present invention provides an electromagnetic wave absorbing paint, coating, preparation method and application based on carbon fiber-molybdenum disulfide composite material. The electromagnetic wave absorbing paint provided by the present invention exhibits excellent electromagnetic wave absorption performance in a wide frequency band of 2 to 18 GHz, and has low cost, light weight, strong bonding with the substrate, and good durability.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] An electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material comprises the following components in mass fraction: 20-30% of the carbon fiber-molybdenum disulfide composite material, 52.5-70% of a polyurethane liquid resin, 0.5-1% of a silane coupling agent, 0.2-0.5% of a defoamer, 0.1-1% of a leveling agent, and 3-15% of a thickener; the carbon fiber-molybdenum disulfide composite material comprises carbon fibers and molybdenum disulfide grown on the surface of the carbon fibers.
[0009] Preferably, the preparation method of the carbon fiber-molybdenum disulfide composite material comprises:
[0010] Dissolving polyacrylonitrile in an organic solvent to obtain a precursor spinning solution;
[0011] Electrospinning the precursor spinning solution to obtain polyacrylonitrile-based fibers;
[0012] The polyacrylonitrile fiber is sequentially dried, pre-oxidized and carbonized to obtain carbon fiber;
[0013] Mixing a molybdenum source, a sulfur source, a quaternary ammonium salt and water to obtain a mixed solution;
[0014] The carbon fiber is immersed in the mixed solution and then subjected to a hydrothermal reaction to obtain the carbon fiber-molybdenum disulfide composite material.
[0015] Preferably, the concentration of the precursor spinning solution is 0.05-0.2 g / mL; the voltage of the electrospinning is 10-30 kV; the temperature of the pre-oxidation is 200-300° C., and the time is 1-3 h; the temperature of the carbonization is 800-900° C., and the time is 1-3 h, and the carbonization atmosphere is nitrogen;
[0016] The mass ratio of the molybdenum source, the sulfur source and the quaternary ammonium salt is 1:2-4:0.01-0.05; the temperature of the hydrothermal reaction is 180-250° C., and the time is 24-48 hours.
[0017] Preferably, the polyurethane liquid resin includes one or more of a thermosetting polyurethane resin, an aromatic polyurethane resin, a waterborne polyurethane resin and an aliphatic polyurethane resin;
[0018] The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0019] The leveling agent includes one or more of an organic silicon leveling agent, a polyether leveling agent and a fluoride leveling agent.
[0020] The thickener includes one or more of carboxymethyl cellulose, polyurethane thickener, polyacrylate thickener and xanthan gum;
[0021] The viscosity of the electromagnetic wave absorbing paint is 500-1500 mPa s.
[0022] Preferably, the components of the electromagnetic wave absorbing coating also include 0.2 to 10% of functional additives; the functional additives include one or more of high temperature resistant additives and antioxidants; the high temperature resistant additives are inorganic aluminum-containing compounds; the antioxidants include one or more of phenolic antioxidants and phosphite antioxidants.
[0023] The present invention also provides a method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme, comprising the following steps: mixing the components to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
[0024] The present invention also provides an electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material, characterized in that it is formed by the electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material described in the above scheme.
[0025] The present invention also provides a method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme, comprising the following steps:
[0026] The electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material is coated on the surface of the substrate and then cured to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
[0027] Preferably, the coating speed is 10 to 100 cm / min; the coating thickness is 1.5 to 2.0 mm; the substrate is a flexible substrate; the curing temperature is 60 to 85° C., and the curing time is 2 to 4 hours.
[0028] The present invention also provides the application of the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme in the field of electromagnetic wave absorption.
[0029] The present invention provides an electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material, comprising the following components by mass fraction: 20-30% of a carbon fiber-molybdenum disulfide composite material, 50-70% of a polyurethane liquid resin, 0.5-1% of a silane coupling agent, 0.2-0.5% of a defoaming agent, 0.1-1% of a leveling agent, and 3-15% of a thickener; the carbon fiber-molybdenum disulfide composite material comprises carbon fibers and molybdenum disulfide grown on the surface of the carbon fibers. The beneficial effects of the electromagnetic wave absorbing coating provided by the present invention are as follows:
[0030] It has excellent electromagnetic wave absorption performance in a wide frequency band: carbon fiber has the characteristics of good conductivity, light weight and good mechanical properties; molybdenum disulfide is a new type of two-dimensional material with good dielectric and magnetic loss characteristics, and its layered structure can enhance the polarization loss and interface effect of the material. The present invention combines carbon fiber with molybdenum disulfide to form a composite material with good impedance matching, lightweight and broadband wave absorption ability, combines the excellent conductivity of carbon fiber and the dielectric and magnetic loss characteristics of molybdenum disulfide, forms multiple electromagnetic wave loss mechanisms, effectively improves the absorption efficiency of electromagnetic waves, and realizes effective wave absorption in the wide frequency band of 2 to 18 GHz, especially in the high frequency band (above 10 GHz). The electromagnetic wave absorption performance is significantly enhanced, which can meet the needs of modern stealth equipment and wireless communication equipment for broadband absorption.
[0031] Excellent impedance matching: The electromagnetic wave absorbing coating of the present invention can match the impedance of free space in a wide frequency range, minimize reflection and improve the absorption efficiency of electromagnetic waves. Good impedance matching ensures the stable performance of the coating in different application environments and significantly improves the wave absorption effect.
[0032] Lightweight: Traditional electromagnetic wave absorbing materials such as ferrites and carbon-based materials generally have the problems of high density and heavy weight, and are not suitable for the demand for lightweight materials in modern applications, especially in the fields of aerospace, stealth equipment, etc. The present invention uses carbon fiber as the matrix material. Carbon fiber has excellent mechanical properties and low density. The coating formed has low density, light weight and good mechanical properties. Therefore, the electromagnetic wave absorbing coating of the present invention solves the problem of heavy weight and insufficient performance of existing absorbing materials, and is suitable for scenes with high weight requirements, such as aerospace and military equipment.
[0033] Applicable to complex surfaces and easy to use: Traditional absorbing materials are mostly in solid or powder form, which is inconvenient to use and difficult to apply to complex surfaces. The electromagnetic wave absorbing coating provided by the present invention can be used by coating, can be easily applied to various complex surfaces, and is suitable for flexible substrates (such as fabrics and glass fibers), broadening the application scenarios of the material.
[0034] Strong adhesion and good durability: The present invention introduces a silane coupling agent into the coating, which can enhance the adhesion between the coating and the substrate, and optimizes the durability of the coating, so that it can still maintain excellent electromagnetic wave absorption performance in harsh environments such as high temperature, acid and alkali; further, the present invention also adds high temperature resistant additives and antioxidants to the coating, which can further improve the environmental adaptability of the coating. The results of the embodiment show that the coating formed by the coating of the present invention can still maintain excellent electromagnetic wave absorption performance in harsh environments such as high temperature, acid and alkali, and is suitable for use under complex and harsh conditions, ensuring its stability in long-term application.
[0035] Low cost: The carbon fiber-molybdenum disulfide composite material used in the present invention is formed by compounding carbon fiber and molybdenum disulfide. Molybdenum disulfide not only has a two-dimensional structure similar to graphene, which can achieve a good polarization effect, but also has stronger high-frequency wave absorbing performance. Compared with graphene, the preparation cost of molybdenum disulfide is lower, the composite process is easier to control, and stable large-scale production can be achieved, thereby improving economy and consistency.
[0036] In summary, the electromagnetic wave absorbing coating provided by the present invention has excellent absorption capacity in a wide frequency band, and has a light structure and good impedance matching. The absorption frequency band range can be adjusted by controlling the coating thickness. At the same time, the coating is light in weight, strong in adhesion, good in durability, easy to use, and low in cost. It is suitable for application in high-tech fields such as aerospace, stealth equipment, and electromagnetic interference shielding. The electromagnetic wave absorbing coating of the present invention has shown breakthrough progress in material design, performance improvement, environmental adaptability, and economy, and has broad application prospects and market potential, providing a new solution for the research and development and application of electromagnetic wave absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a SEM image of the carbon fiber-molybdenum disulfide composite material prepared in Example 1;
[0038] Figure 2 The electromagnetic parameter test results of carbon fiber-molybdenum disulfide composite materials, where (a) is the real part of dielectric constant, (b) is the imaginary part of dielectric constant, (c) is the dielectric loss factor, (d) is the real part of magnetic permeability, (e) is the imaginary part of magnetic permeability, (f) is the magnetic loss factor, (g) is the Cole-Cole curve, (h) is the C0 curve, and (i) is the attenuation constant;
[0039] Figure 3 The reflection loss (RL) and impedance matching characteristics test results of carbon fiber-MoS2 composite materials, where (a) is the 3D RL curve, (b) is the 2D RL curve, and (c) is the |Δ| impedance matching diagram;
[0040] Figure 4 This is the reflection loss curve of carbon fiber-molybdenum disulfide composite material at different matching thicknesses. DETAILED DESCRIPTION
[0041] The invention provides an electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material, comprising the following components in mass fraction: 20-30% of the carbon fiber-molybdenum disulfide composite material, 52.5-70% of a polyurethane liquid resin, 0.5-1% of a silane coupling agent, 0.2-0.5% of a defoamer, 0.1-1% of a leveling agent, and 3-15% of a thickener; the carbon fiber-molybdenum disulfide composite material comprises carbon fibers and molybdenum disulfide grown on the surface of the carbon fibers.
[0042] In terms of mass fraction, the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material provided by the present invention includes 20% to 30% of the carbon fiber-molybdenum disulfide composite material, specifically 20%, 22%, 25% or 30%; the carbon fiber-molybdenum disulfide composite material includes carbon fiber and molybdenum disulfide grown on the surface of the carbon fiber, and the molybdenum disulfide is a nanostructure, specifically in the form of nanosheets or nanoflowers; specifically, the diameter of the carbon fiber is preferably 400 to 600 nm, and the size of the molybdenum disulfide is preferably 1 to 10 nm.
[0043] In the present invention, the method for preparing the carbon fiber-molybdenum disulfide composite material preferably comprises:
[0044] Dissolving polyacrylonitrile in an organic solvent to obtain a precursor spinning solution;
[0045] Electrospinning the precursor spinning solution to obtain polyacrylonitrile-based fibers;
[0046] The polyacrylonitrile fiber is sequentially dried, pre-oxidized and carbonized to obtain carbon fiber;
[0047] Mixing a molybdenum source, a sulfur source, a quaternary ammonium salt and water to obtain a mixed solution;
[0048] The carbon fiber is immersed in the mixed solution and then subjected to a hydrothermal reaction to obtain the carbon fiber-molybdenum disulfide composite material.
[0049] In the present invention, the organic solvent is preferably N,N-dimethylformamide (DMF), and the concentration of the precursor spinning solution is preferably 0.05-0.2g / mL, specifically 0.1g / mL; the present invention preferably adds polyacrylonitrile to DMF and stirs for 12h to obtain the precursor spinning solution. In the present invention, the voltage of the electrospinning is preferably 10-30kV, specifically 15kV or 20kV. In the present invention, the drying temperature is preferably 60°C. In the present invention, the pre-oxidation temperature is preferably 200-300°C, specifically 250°C or 260°C, and the pre-oxidation time is preferably 1-3h, specifically 2h. The present invention can improve the thermal stability of polyacrylonitrile fiber by pre-oxidation, and prevent the fiber from melting or deforming during carbonization. In the present invention, the carbonization temperature is preferably 800-900°C, specifically 850°C, and the carbonization time is preferably 1-3h, specifically 2h; the carbonization atmosphere is preferably nitrogen.
[0050] In the present invention, the molybdenum source is preferably ammonium molybdate; the sulfur source is preferably thiourea; the quaternary ammonium salt is preferably one or more of cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), tetraethylammonium chloride (TEACl) and dodecyltrimethylammonium chloride (DTAC). By adding the quaternary ammonium salt, the surface of the carbon fiber can be positively charged, which is beneficial to the growth of molybdenum disulfide.
[0051] In the present invention, the mass ratio of the molybdenum source, the sulfur source and the quaternary ammonium salt is preferably 1:2-4:0.01-0.05, specifically 1:3:0.01; the amount ratio of the molybdenum source and water is preferably 1g:50-100mL, more preferably 1g:80mL; the soaking time is preferably 0.5-2h, more preferably 1h, and the soaking is preferably carried out under ultrasonic conditions. In the present invention, the temperature of the hydrothermal reaction is preferably 180-250°C, specifically 200°C, the time of the hydrothermal reaction is preferably 24-48h, specifically 24h or 36h, and the hydrothermal reaction is preferably carried out in a PTFE-lined reactor; after the hydrothermal reaction is completed, the obtained product is preferably washed with water to obtain the carbon fiber-molybdenum disulfide composite material. In a specific embodiment of the present invention, the polyacrylonitrile-based fiber obtained by electrospinning is in the form of a fiber membrane, and thus the finally obtained carbon fiber-molybdenum disulfide composite material is also in the form of a film. The present invention preferably shears or grinds the film-like carbon fiber-molybdenum disulfide composite material to improve the dispersibility of the carbon fiber-molybdenum disulfide composite material in the polyurethane liquid resin.
[0052] When synthesizing molybdenum disulfide by traditional chemical synthesis method, it is easy to cause aggregation of molybdenum disulfide nanosheets, which affects the electromagnetic wave absorption performance of the composite material. The present invention adopts a hydrothermal method to synthesize the carbon fiber-molybdenum disulfide composite material, and controls the morphology and distribution of molybdenum disulfide by optimizing the reaction conditions to ensure the uniform growth and dispersion of molybdenum disulfide nanosheets, thereby ensuring the structural stability of the carbon fiber-molybdenum disulfide composite material, and then ensuring that the composite material has stable electromagnetic wave absorption performance in a wide frequency band. At the same time, the structural stability of the composite material can also ensure the performance of the coating under extreme conditions and improve the environmental tolerance of the coating.
[0053] The polyurethane liquid resin includes one or more of thermosetting polyurethane resin, aromatic polyurethane resin, waterborne polyurethane resin and aliphatic polyurethane resin.
[0054] In terms of mass fraction, the electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material provided by the present invention includes 52.5-70% of polyurethane liquid resin, specifically 56%, 61% or 66%. In the present invention, the solid content of the polyurethane liquid resin is preferably 30-70%, more preferably 40-60%; the polyurethane liquid resin preferably includes one or more of thermosetting polyurethane liquid resin, aromatic polyurethane liquid resin, waterborne polyurethane liquid resin and aliphatic polyurethane liquid resin, more preferably waterborne polyurethane liquid resin. In a specific embodiment of the present invention, the waterborne polyurethane liquid resin is purchased from McLean, model A909856. In the present invention, waterborne polyurethane has good environmental protection and low volatile organic compound (VOC) emissions, meeting green environmental protection requirements. In addition, the application of waterborne polyurethane in coatings can provide excellent mechanical properties, water resistance and aging resistance, while having good flexibility and adhesion, and is suitable for the coating requirements of flexible substrates. Compared with solvent-based polyurethane, waterborne polyurethane also has lower odor and a more controllable coating process. Epoxy resin is usually used as the polymer matrix in traditional electromagnetic wave absorbing materials, but epoxy resin performs poorly in toughness and flexibility and is not suitable for combination with carbon fiber-molybdenum disulfide composite materials. The present invention uses polyurethane liquid resin as the matrix. Polyurethane liquid resin has excellent flexibility and adhesion, can improve the flexibility, adhesion and durability of the coating, and is particularly suitable for coating of flexible substrates.
[0055] In terms of mass fraction, the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material provided by the present invention includes 0.5-1% of a silane coupling agent; the silane coupling agent preferably includes one or more of γ-aminopropyltriethoxysilane (KH550) and γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560); by adding a silane coupling agent, the present invention can improve the interfacial bonding force between the carbon fiber-molybdenum disulfide composite material and the resin matrix, ensure the uniform dispersion of the carbon fiber-molybdenum disulfide composite material in the coating, and improve the durability and adhesion of the coating. In the present invention, if the amount of silane coupling agent added is too much, it will affect the rheology of the coating. The present invention controls the amount of silane coupling agent within the above range, which can improve the adhesion and durability of the coating while ensuring the operability and uniformity of the coating.
[0056] In terms of mass fraction, the electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material provided by the present invention includes 0.2-0.5% of defoamer, specifically 0.2%, 0.3% or 0.5%; the defoamer preferably includes one or more of an oily defoamer and an aqueous defoamer, more preferably an aqueous defoamer, and the aqueous defoamer is preferably a silicon-based defoamer. The present invention has no special requirements for the specific type of the silicon-based defoamer, and it can be used as those familiar to those skilled in the art. In a specific embodiment of the present invention, the silicon-based defoamer used is Dow AFE-1410. In the present invention, the defoamer is used to eliminate bubbles generated during the stirring and coating process of the coating, to ensure the uniformity and flatness of the coating, thereby avoiding affecting the wave absorbing effect and mechanical properties of the coating; the present invention controls the amount of defoamer added within the above range, which can effectively eliminate bubbles while maintaining the stability of the coating. Excessive addition of the defoamer will reduce the rheology of the coating.
[0057] In terms of mass fraction, the electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material provided by the present invention includes 0.1-1% of leveling agent; the leveling agent preferably includes one or more of organic silicon leveling agent, polyether leveling agent and fluoride leveling agent; the present invention has no special requirements for the specific types of the organic silicon leveling agent, polyether leveling agent and fluoride leveling agent, and those familiar to those skilled in the art can be used. In a specific embodiment of the present invention, the leveling agent is BYK-320 or LP-320. The addition of the leveling agent in the present invention can ensure uniform coating of the coating on the flexible substrate, avoid uneven thickness, and improve the smoothness of the coating surface.
[0058] In terms of mass fraction, the electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material provided by the present invention includes 3-15% thickener, and the specific addition amount is determined according to actual needs. In a specific embodiment of the present invention, the amount of the thickener is based on controlling the viscosity of the electromagnetic wave absorbing coating to 500-1500mPa s; the leveling agent preferably includes one or more of carboxymethyl cellulose, polyurethane thickener, polyacrylate thickener and xanthan gum, and more preferably polyurethane thickener. The present invention has no special requirements for the specific types of the carboxymethyl cellulose, polyurethane thickener, polyacrylate thickener and xanthan gum thickener, and those familiar to those skilled in the art can be used. In a specific embodiment of the present invention, the thickener used is Coapur2501, a high-Tai polyurethane thickener. The present invention adds a thickener to increase the viscosity of the coating, improve the fluidity and application performance of the coating, thereby ensuring uniformity and stability during the coating process.
[0059] In the present invention, the components of the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material preferably further include 0.2-10% of functional additives; the functional additives preferably include one or more of high temperature resistant additives and antioxidants; specifically, the addition amount of the high temperature resistant additive is preferably 1-10wt%, and the addition amount of the antioxidant is preferably 0.2-2wt%; the high temperature resistant additive is preferably an inorganic aluminum-containing compound; the inorganic aluminum-containing compound is preferably one or both of aluminum silicate and aluminum oxide, and the aluminum oxide is preferably used in the form of bauxite powder; the antioxidant preferably includes one or more of phenolic antioxidants and phosphite antioxidants, and the phenolic antioxidant preferably includes one or more of 2,6-di-tert-butyl-4-methylphenol (BHT) and antioxidant 1010. The present invention can improve the tolerance of the coating in a high temperature environment by adding a high temperature resistant additive, avoid the performance degradation at high temperature, and avoid the phenomenon of peeling and embrittlement; by adding an antioxidant, the durability of the coating can be enhanced to ensure the stability of the coating in various environments.
[0060] The present invention also provides a method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme, comprising the following steps: mixing the components to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
[0061] In a specific embodiment of the present invention, it is preferred to first mix the carbon fiber-molybdenum disulfide composite material and the polyurethane liquid resin, and then add the silane coupling agent, the defoaming agent and the leveling agent, and stir evenly; when the coating also includes a functional additive, it is preferred to first mix the carbon fiber-molybdenum disulfide composite material, the polyurethane liquid resin and the functional additive, and then add the silane coupling agent, the defoaming agent and the leveling agent and stir evenly.
[0062] The present invention also provides an electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material, which is formed by the electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material described in the above scheme. In the present invention, the density of the electromagnetic wave absorbing coating based on a carbon fiber-molybdenum disulfide composite material is ≤1.2g / cm 3 , preferably 1.1 to 1.2 g / cm 3 ,
[0063] The present invention also provides a method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme, comprising the following steps:
[0064] The electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material is coated on the surface of the substrate and then cured to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
[0065] In the present invention, the substrate is preferably a flexible substrate. The present invention has no special requirements on the type of the flexible substrate, which can be fabric, glass fiber, polymer film, etc.; the coating method is preferably a blade coating method; the coating speed is preferably 10 to 100 cm / min; in a specific embodiment of the present invention, when the viscosity of the electromagnetic wave absorbing coating is greater than 1000 mPa s and less than or equal to 1500 mPa s, the coating speed is preferably 50 to 100 cm / min, and when the viscosity of the electromagnetic wave absorbing coating is greater than or equal to 500 mPa s and less than or equal to 1000 mPa s, the coating speed is preferably 10 to 30 cm / min; the present invention adopts the above coating speed to achieve uniform coating of the coating.
[0066] In the present invention, the coating thickness is preferably 1.5 to 2.0 mm. The present invention controls the coating thickness within the above range, which can ensure the performance of the coating and avoid the occurrence of sagging caused by an overly thick coating.
[0067] In the present invention, the curing temperature is preferably 60 to 85° C., more preferably 70 to 80° C., and the curing time is preferably 2 to 4 hours, more preferably 2 to 3 hours. The present invention controls the curing temperature and time within the above ranges to ensure uniform curing of the coating layer, reduce the internal stress of the coating layer, and avoid cracking of the coating layer.
[0068] The traditional preparation process of electromagnetic wave absorbing materials is complex, costly, and difficult to mass produce. The present invention prepares the electromagnetic wave absorbing coating through a blade coating method, which has a simple and easy operation process and is suitable for large-scale industrial production. It significantly reduces the preparation cost and time and improves production efficiency.
[0069] The present invention also provides the application of the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material described in the above scheme in the field of electromagnetic wave absorption; in a specific embodiment of the present invention, the electromagnetic wave absorbing coating can be specifically used in stealth equipment, electromagnetic interference (EMI) shielding of electronic equipment, wireless communication antenna isolation, transportation, building materials or medical equipment. The following is a detailed description:
[0070] Stealth equipment: In the military field, radar stealth coating is a key means to reduce the probability of a target being detected by radar. Electromagnetic wave absorbing materials are an important component of radar stealth coatings, which can absorb or attenuate radar waves, thereby reducing the radar reflection signal of the target; the electromagnetic wave absorbing coating provided by the present invention has lightweight and wide-band electromagnetic wave absorption performance, and is particularly suitable for stealth coatings for aircraft, ships, missiles and other equipment to enhance their radar stealth capabilities.
[0071] Electromagnetic interference (EMI) shielding of electronic devices: With the widespread application of electronic devices, the problem of electromagnetic interference has become more and more serious, especially in high-frequency communications, precision instruments and power systems, where electromagnetic waves may interfere with the normal operation of the equipment, resulting in data loss or functional disorders. The electromagnetic wave absorbing coating of the present invention has excellent electromagnetic wave absorption performance, can effectively shield or absorb electromagnetic waves around the equipment, reduce electromagnetic interference, and protect the stable operation of electronic components; at the same time, because the coating has good mechanical properties, it can also be used in electronic devices that require high strength and lightweight design.
[0072] Wireless communication antenna isolation: In 5G and future communication technologies, signal interference between wireless antennas is a common problem, especially in high-frequency bands, where the signals of antenna arrays will affect each other, resulting in a decrease in signal quality. The electromagnetic wave absorbing coating of the present invention can be used for the absorbing coating or shielding device of wireless communication base station antennas to absorb unnecessary electromagnetic signals, thereby improving the isolation between antennas and enhancing the transmission efficiency and stability of signals.
[0073] Transportation: Modern transportation vehicles such as automobiles and airplanes have strict requirements in terms of lightweight and electromagnetic interference control. For example, high-frequency current and voltage changes in electric vehicles will generate strong electromagnetic radiation, affecting the stability of the vehicle's internal electronic system. The electromagnetic wave absorbing coating provided by the present invention can be applied to the outer shell or internal components of a vehicle to help absorb the electromagnetic radiation generated by the vehicle and prevent interference with internal electronic equipment. At the same time, the lightweight characteristics of the coating help improve the energy efficiency of vehicles.
[0074] Building field: With the popularization of smart buildings and Internet of Things devices, the electromagnetic environment inside buildings has become more and more complex, which can easily cause electromagnetic interference between devices and affect the stability of the system. The electromagnetic wave absorbing coating of the present invention can be used for the wall or partition coating of a building to shield the electromagnetic radiation from the outside world or adjacent equipment, forming an efficient electromagnetic shielding structure to ensure the electromagnetic compatibility of the indoor environment.
[0075] Medical equipment: Medical equipment, such as MRI (magnetic resonance imaging) and CT scanners, are easily interfered by external electromagnetic waves, which may affect the imaging effect or the accuracy of the equipment. The electromagnetic wave absorbing coating of the present invention can be applied to the housing of medical equipment or specific protective components to absorb and shield unnecessary electromagnetic wave interference, ensuring the precise and stable operation of the medical equipment.
[0076] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0077] The polyurethane used in the following examples is a water-based polyurethane (A909856) purchased from MacLean.
[0078] The carbon fiber-molybdenum disulfide composite material used in the following examples is prepared as follows:
[0079] Dissolve 1g of polyacrylonitrile (PAN) in 10mL of DMF and stir for 12h to obtain a precursor spinning solution. Electrospin the precursor spinning solution at a static voltage of 20kV to obtain PAN-based fibers. Dry the obtained PAN-based fibers at 60°C and heat at 260°C for 2h to obtain pre-oxidized fibers. Carbonize the pre-oxidized fibers at 850°C for 2h in a N2 atmosphere to obtain a carbon fiber membrane.
[0080] 1g ammonium molybdate, 2g thiourea, 0.01g CTAB and 80mL water were prepared into a mixed solution, and the carbon fiber membrane was immersed in the mixed solution and ultrasonically treated for 1h. Then it was transferred to a PTFE-lined reactor and reacted at 200℃ for 24h. After the reaction, the product was washed with distilled water several times to obtain a carbon fiber-molybdenum disulfide composite material; the carbon fiber-molybdenum disulfide composite material was broken up when preparing the coating.
[0081] Figure 1 This is a SEM image of the carbon fiber-molybdenum disulfide composite material prepared in Example 1. It can be clearly observed from the SEM image that the carbon fiber matrix presents a mesh or fibrous structure, and the surface is covered with a nano-scale branched or flower-like nanostructure, which corresponds to the growth of molybdenum disulfide (molybdenum disulfide nanosheets or nanoflowers) on the carbon fiber; this morphology shows that the deposition of molybdenum disulfide on the surface of the carbon fiber is relatively uniform, which helps to increase the specific surface area of the composite material, thereby improving its performance in electromagnetic wave absorption applications. The diameter of the carbon fiber is roughly 400-600nm, and the diameter of the molybdenum disulfide nanostructure covered on the surface is relatively small, about 1-10nm. The above results show that the carbon fiber-molybdenum disulfide composite material prepared by the present invention has a large specific surface area, can effectively interact with electromagnetic waves, and enhance the wave absorption performance; at the same time, the carbon fiber as a supporting skeleton can provide high mechanical strength and excellent conductivity, and molybdenum disulfide as a functional material improves the electromagnetic loss capacity of the composite material through its layered structure and semiconductor properties.
[0082] The electromagnetic parameters of carbon fiber-molybdenum disulfide composite materials were tested by coaxial line method. The results are as follows: Figure 2 As shown, Figure 2 Where (a) is the real part of the dielectric constant, (b) is the imaginary part of the dielectric constant, (c) is the dielectric loss factor, (d) is the real part of the magnetic permeability, (e) is the imaginary part of the magnetic permeability, (f) is the magnetic loss factor, (g) is the Cole-Cole curve, (h) is the C0 curve, and (i) is the attenuation constant.
[0083] The electromagnetic wave absorption performance is usually determined by the complex dielectric constant (ε r =ε′-jε″) and complex magnetic permeability (μ r =μ′-jμ″). The real part of the electromagnetic parameter (ε' and μ') represents the energy storage capacity, and the imaginary part (ε" and μ") represents the energy loss capacity. Figure 2 From (a) to (c), it can be found that the composite material exhibits stable dielectric properties in the range of 2 to 18 GHz, and ε" fluctuates at some frequencies, indicating that the material can effectively absorb electromagnetic energy. These characteristics show that the carbon fiber-molybdenum disulfide composite material has good dielectric loss and is conducive to electromagnetic wave absorption. Figure 2 (d) and (e) show that the real and imaginary values of the magnetic permeability remain relatively stable throughout the frequency band, indicating that the carbon fiber-molybdenum disulfide composite material also has certain capabilities in magnetic loss, and may improve the electromagnetic wave absorption performance through the synergistic effect of dielectric and magnetic losses. Figure 2 (f) in the figure shows that the magnetic loss factor has the same fluctuation as the imaginary part of the magnetic permeability and its value is smaller than Figure 2 The dielectric loss factor shown in (e) indicates that dielectric loss plays a dominant role in electromagnetic wave attenuation. Figure 2 Each semicircle in the Cole-Cole curve shown in (g) represents a polarization loss mode. It can be seen that the composite material has a variety of polarization losses, and the rich loss mechanism improves the absorption capacity of the composite material. Figure 2 It can be seen from the C0 curve shown in (h) that there are fluctuations at lower frequencies, indicating that resonance loss dominates the magnetic loss, and the C0 curve at higher frequencies is almost unchanged, indicating that eddy current loss dominates. Figure 2 (i)) increases with the increase of frequency, especially in the high frequency band (>10GHz), which shows a significant increase, indicating that the material has a strong ability to absorb electromagnetic waves in the high frequency range.
[0084] The electromagnetic wave absorption performance can be expressed by reflection loss (RL), which is calculated by the following formula:
[0085]
[0086] Among them, Z0 and Z inrefers to the free space impedance and input impedance of the absorber, j refers to the imaginary unit, c is the speed of light, d is the matching thickness, and f is the frequency of the electromagnetic wave; μ r is the complex magnetic permeability of the material, ε r is the complex dielectric constant of the material, and h is Planck's constant.
[0087] Minimum reflection loss (RL min ) refers to the minimum value of electromagnetic wave reflection loss, which characterizes the maximum value of the electromagnetic wave absorption capacity of the material. When the RL value is less than -10dB, the electromagnetic wave absorption reaches 90%. Therefore, -10dB is a threshold value, below which electromagnetic wave absorption can be effectively achieved. The frequency range below this value is defined as the effective absorption bandwidth (EAB), and EAB max Indicates the maximum effective absorption bandwidth.
[0088] Based on the above formula, the RL curves of 3D and 2D carbon fiber-molybdenum disulfide composites were plotted. The results are as follows Figure 3 As shown in (a) and (b) in the figure. Figure 3 As can be seen from (a) and (b), the RL of carbon fiber-MoS2 composites min Reached -62.43dB, EAB max Reached 5.54GHz.
[0089] The impedance matching characteristic reflects the penetration of electromagnetic waves into materials. Theoretically, perfect impedance matching of materials can lead to zero reflection of electromagnetic waves, allowing electromagnetic waves to fully enter the composite material and be absorbed. The impedance matching diagram of carbon fiber-molybdenum disulfide composite material is drawn using the following formula:
[0090] |Δ|=|sinh 2 (Kfd)-M|
[0091]
[0092] Where: h is Planck's constant, f is the frequency of the electromagnetic wave, d is the matching thickness, μ' is the real part of the magnetic permeability, ε' is the real part of the dielectric constant, δ e is the phase angle of the electric field, δ m is the phase angle of the magnetic field.
[0093] The |Δ| impedance matching diagram is drawn as Figure 3 As shown in (c), the closer the |Δ| impedance matching value is to 0, the better the impedance matching of the composite material is. Figure 3 As can be seen from (c), the carbon fiber-molybdenum disulfide composite material of the present invention has good impedance matching characteristics.
[0094] Figure 4is the reflection loss curve of carbon fiber-MoS2 composite material at different matching thicknesses. Figure 4 It can be seen that the composite material with a matching thickness of 3.6 mm achieves the best RL min , matching the composite material with a thickness of 1.5mm to achieve the best EAB.
[0095] Example 1
[0096] The components of the electromagnetic wave absorbing coating are: 20wt% carbon fiber-molybdenum disulfide composite material, 66% polyurethane liquid resin, 1% silane coupling agent, 0.5wt% silicon-based defoamer, 0.5wt% leveling agent, and 12% polyurethane thickener, wherein the silane coupling agent is KH550, the silicon-based defoamer is Dow AFE-1410, the leveling agent is BYK-320, and the thickener is Coapur2501, a high-performance polyurethane thickener.
[0097] The preparation method of the electromagnetic wave absorbing coating is as follows: the carbon fiber-molybdenum disulfide composite material and the polyurethane liquid resin are uniformly mixed, and then a silane coupling agent, a silicon-based defoaming agent, a leveling agent and a thickener are added, and the mixture is stirred in a mixer at a speed of 1000 rpm for 30 minutes to obtain the electromagnetic wave absorbing coating.
[0098] Preparation of electromagnetic wave absorbing coating: The electromagnetic wave absorbing coating was coated on a flexible substrate (polyester fiber fabric) using a blade coating method at a coating rate of 100 cm / min and a coating thickness of 2.0 mm. It was then cured at 80°C for 2 h to obtain an electromagnetic wave absorbing coating.
[0099] The coaxial probe method was used to test the wave absorption performance of the coating, the tape stripping method was used to test the adhesion, the thermal aging hardness was used to test the high temperature resistance (the thermal aging temperature was 200°C and the time was 300h), the electrochemical workstation was used to test the corrosion resistance (the acidic solution was HCl solution and the alkaline solution was NaOH solution), and the Archimedes method was used to test the coating density.
[0100] Performance Testing
[0101] Electromagnetic wave absorption performance: minimum reflection loss is -55.3dB, and absorption bandwidth is 4.8GHz.
[0102] Adhesion test: The adhesion of the coating is 8MPa.
[0103] High temperature resistance test: The coating remained stable at 200°C without obvious embrittlement or peeling, and the hardness change was 6%, indicating its good high temperature resistance.
[0104] Corrosion resistance test:
[0105] In an acidic solution with pH = 1, the polarization resistance of the coating is 534.7Ω·cm2 , corrosion current is 0.25μA / cm 2 The coating of the present invention shows good acid corrosion resistance.
[0106] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 589.5Ω·cm 2 , the corrosion current is 0.24μA / cm 2 The coating of the present invention has good alkaline corrosion resistance.
[0107] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 576.3Ω·cm 2 , corrosion current is 0.22μA / cm 2 The coating of the present invention has good sea water corrosion resistance.
[0108] Density test: coating density is 1.2g / cm 3 , while the density of pure polyurethane liquid resin coating is 1.3g / cm 3 Compared with pure polyurethane liquid resin, the coating density of the present invention is reduced by about 7.69%, and has lightweight characteristics.
[0109] Example 2
[0110] The components of the electromagnetic wave absorbing coating are: 25wt% carbon fiber-molybdenum disulfide composite material, 61% polyurethane liquid resin, 1% silane coupling agent, 0.5wt% silicon-based defoamer, 0.5wt% leveling agent, and 12% thickener; the types of silane coupling agent, silicon-based defoamer, leveling agent and thickener are the same as those in Example 1.
[0111] The preparation method of the electromagnetic wave absorbing paint and coating is the same as that in Example 1.
[0112] Performance Testing
[0113] Electromagnetic wave absorption performance: minimum reflection loss is -58.4dB, and absorption bandwidth is 5.2GHz.
[0114] Adhesion test: The adhesion of the coating is 8MPa.
[0115] High temperature resistance test: The coating remained stable at 200°C without obvious embrittlement or peeling, and the hardness change was 5.8%, indicating its good high temperature resistance.
[0116] Electrochemical corrosion test:
[0117] In an acidic solution with pH = 1, the polarization resistance of the coating is 554.3Ω·cm 2 , corrosion current is 0.2μA / cm 2, showing that the coating has good corrosion resistance in acidic environment.
[0118] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 588.6Ω·cm 2 , corrosion current is 0.22μA / cm 2 , showing good alkali resistance.
[0119] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 583.2Ω·cm 2 , corrosion current is 0.2μA / cm 2 , showing good resistance to salt water corrosion.
[0120] Density test: coating density is 1.18g / cm 3 .
[0121] Example 3
[0122] The components of the electromagnetic wave absorbing coating are: 30wt% of carbon fiber-molybdenum disulfide composite material, 56% of polyurethane liquid resin, 1% of KH550 silane coupling agent, 0.5wt% of silicon-based defoaming agent, 0.5wt% of leveling agent, and 12% of polyurethane thickener; the types of silane coupling agent, silicon-based defoaming agent, leveling agent and thickener are the same as those in Example 1.
[0123] The preparation method of the electromagnetic wave absorbing paint and coating is the same as that in Example 1.
[0124] Performance Testing
[0125] Electromagnetic wave absorption performance: minimum reflection loss is -62.6dB, and absorption bandwidth is 5.5GHz.
[0126] Adhesion test: The adhesion of the coating is 8.1MPa.
[0127] High temperature resistance test: The coating remained stable at 200°C without obvious embrittlement or peeling, and the hardness change was 5.8%, indicating its good high temperature resistance.
[0128] Electrochemical corrosion test:
[0129] In an acidic solution with pH = 1, the polarization resistance of the coating is 564.3Ω·cm 2 , corrosion current is 0.18μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0130] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 589.3Ω·cm 2 , corrosion current is 0.17μA / cm 2 , showing good alkali resistance.
[0131] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 578.2Ω·cm 2 , corrosion current is 0.17μA / cm 2 , showing good resistance to salt water corrosion.
[0132] Density test: coating density is 1.1g / cm 3 .
[0133] Comparative Example 1: Coating using only carbon fiber substrate
[0134] Other conditions are the same as those in Example 3, except that the carbon fiber-molybdenum disulfide composite material is replaced by carbon fiber, and the coating and curing processes are the same as those in Example 3.
[0135] Performance Testing
[0136] Electromagnetic wave absorption performance: the minimum reflection loss is -18.2 dB, the absorption bandwidth is 3.8 GHz, and the electromagnetic wave absorption performance is significantly reduced compared with Examples 1 to 3.
[0137] Adhesion test: The coating adhesion is 7.9MPa.
[0138] High temperature resistance: tested at 200℃, there is no obvious embrittlement or peeling phenomenon, and the coating hardness changes by 6%.
[0139] Electrochemical corrosion test:
[0140] In an acidic solution with pH = 1, the polarization resistance of the coating is 385.5Ω·cm 2 , corrosion current is 0.8μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0141] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 425.2Ω·cm 2 , corrosion current is 0.6μA / cm 2 , showing good alkali resistance.
[0142] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 482.2Ω·cm 2 , corrosion current is 0.55μA / cm 2 , showing good resistance to salt water corrosion.
[0143] Density test: coating density is 1.1g / cm 3 .
[0144] Comparative Example 2: Coating using only molybdenum disulfide
[0145] The other conditions are the same as those in Example 3, except that the carbon fiber-molybdenum disulfide composite material is replaced by molybdenum disulfide nanosheets, and the coating and curing processes are the same as those in Example 3.
[0146] Performance Testing
[0147] Electromagnetic wave absorption performance: the minimum reflection loss is -12dB, the absorption bandwidth is 1.6GHz, and the electromagnetic wave absorption performance is significantly reduced compared with Examples 1 to 3.
[0148] Adhesion test: The coating adhesion is 8MPa.
[0149] High temperature resistance: When tested at 200°C, the coating hardness changes by 7%.
[0150] Electrochemical corrosion test:
[0151] In an acidic solution with pH = 1, the polarization resistance of the coating is 493.6Ω·cm 2 , the corrosion current is 0.34μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0152] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 535.5Ω·cm 2 , corrosion current is 0.35μA / cm 2 , showing good alkali resistance.
[0153] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 502.3Ω·cm 2 , the corrosion current is 0.41μA / cm 2 , showing good resistance to salt water corrosion.
[0154] Density test: coating density is 1.16g / cm 3 .
[0155] Comparative Example 3: Coating without silane coupling agent and other additives
[0156] The electromagnetic wave absorbing coating comprises: 30 wt% carbon fiber-molybdenum disulfide composite material and 70% polyurethane liquid resin.
[0157] The preparation method of the coating and the coating is the same as that of Example 3, except that the addition of the silane coupling agent, the defoaming agent and the leveling agent is omitted.
[0158] Performance Testing
[0159] Electromagnetic wave absorption performance: minimum reflection loss is -59dB, and absorption bandwidth is 5.3GHz.
[0160] Adhesion test: The coating adhesion is 3.5 MPa, which is significantly lower than that of Examples 1 to 3. At the same time, it can be observed that there are many bubbles in the coating, and the flatness and smoothness of the coating are poor.
[0161] High temperature resistance: When tested at 200°C, the coating hardness changes by 7.3%.
[0162] Electrochemical corrosion test:
[0163] In an acidic solution with pH = 1, the polarization resistance of the coating is 554.1Ω·cm 2 , corrosion current is 0.2μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0164] In an alkaline solution with pH = 13, the polarization resistance of the coating is 532.2Ω·cm 2 , corrosion current is 0.2μA / cm 2 , showing good alkali resistance.
[0165] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 525.2Ω·cm 2 , corrosion current is 0.21μA / cm 2 , showing good resistance to salt water corrosion.
[0166] Density test: coating density is 1.1g / cm 3 .
[0167] Comparative Example 4 Composite material using epoxy resin as a matrix
[0168] The other conditions were the same as those in Example 3, except that the polyurethane liquid resin was replaced by epoxy resin, and the coating and curing processes were the same as those in Example 3.
[0169] Performance Testing
[0170] Electromagnetic wave absorption performance: minimum reflection loss is -59dB, and absorption bandwidth is 5.3GHz.
[0171] Adhesion test: The coating adhesion is 4.6MPa, which is weak and the coating is prone to peeling.
[0172] High temperature resistance: When tested at 200°C, epoxy resin-based coatings show high rigidity and are prone to cracking or breaking, which limits the application range of the coating, especially on substrates with complex shapes. The coating hardness changes by 7%.
[0173] Electrochemical corrosion test:
[0174] In an acidic solution with pH = 1, the polarization resistance of the coating is 532.3Ω·cm2 , corrosion current is 0.21μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0175] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 522.3Ω·cm 2 , the corrosion current is 0.24μA / cm 2 , showing good alkali resistance.
[0176] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 535.8Ω·cm 2 , corrosion current is 0.25μA / cm 2 , showing good resistance to salt water corrosion.
[0177] Density test: coating density is 1.13g / cm 3 .
[0178] Example 4: Coating with high temperature resistant additives
[0179] The components of the electromagnetic wave absorbing coating are: 30wt% of carbon fiber-molybdenum disulfide composite material, 53wt% of polyurethane liquid resin, 3wt% of bauxite powder (Al2O3), 1wt% of silane coupling agent, 0.5wt% of silicon-based defoamer, 0.5wt% of leveling agent, and 12% of thickener; the types of silane coupling agent, silicon-based defoamer, leveling agent and thickener are the same as those in Example 1.
[0180] The preparation method of the electromagnetic wave absorbing coating is as follows: the carbon fiber-molybdenum disulfide composite material, the polyurethane liquid resin and the bauxite powder are uniformly mixed, and then a silane coupling agent, a silicon-based defoaming agent and a leveling agent are added, and the mixture is stirred in a mixer at a speed of 1000 rpm for 30 minutes to obtain the electromagnetic wave absorbing coating.
[0181] The preparation conditions of the electromagnetic wave absorbing coating are consistent with those in Example 1.
[0182] Performance Testing
[0183] Electromagnetic wave absorption performance: minimum reflection loss is -58.7dB, and absorption bandwidth is 5.2GHz.
[0184] Adhesion test: The coating adhesion is 7.8MPa.
[0185] High temperature resistance: When tested at 200°C, the coating hardness changes by 3%, showing the best high temperature resistance.
[0186] Electrochemical corrosion test:
[0187] In an acidic solution with pH = 1, the polarization resistance of the coating is 542.8Ω·cm2 , corrosion current is 0.2μA / cm 2 , showing that the coating has good corrosion resistance in acidic environment.
[0188] In an alkaline solution with a pH of 13, the polarization resistance of the coating is 564.2Ω·cm 2 , corrosion current is 0.21μA / cm 2 , showing good alkali resistance.
[0189] In simulated seawater containing 3.5wt% NaCl, the polarization resistance of the coating is 546.2Ω·cm 2 , corrosion current is 0.2μA / cm 2 , showing good resistance to salt water corrosion.
[0190] Density test: coating density is 1.2g / cm 3 .
[0191] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material, characterized in that: The invention comprises the following components in mass fraction: 20-30% of a carbon fiber-molybdenum disulfide composite material, 52.5-70% of a polyurethane liquid resin, 0.5-1% of a silane coupling agent, 0.2-0.5% of a defoaming agent, 0.1-1% of a leveling agent, and 3-15% of a thickener; the carbon fiber-molybdenum disulfide composite material comprises carbon fibers and molybdenum disulfide grown on the surface of the carbon fibers.
2. The electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material according to claim 1, characterized in that: The preparation method of the carbon fiber-molybdenum disulfide composite material comprises: Dissolving polyacrylonitrile in an organic solvent to obtain a precursor spinning solution; Electrospinning the precursor spinning solution to obtain polyacrylonitrile-based fibers; The polyacrylonitrile fiber is sequentially dried, pre-oxidized and carbonized to obtain carbon fiber; Mixing a molybdenum source, a sulfur source, a quaternary ammonium salt and water to obtain a mixed solution; The carbon fiber is immersed in the mixed solution and then subjected to a hydrothermal reaction to obtain the carbon fiber-molybdenum disulfide composite material.
3. The electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material according to claim 2, characterized in that: The concentration of the precursor spinning solution is 0.05-0.2 g / mL; the voltage of the electrospinning is 10-30 kV; the temperature of the pre-oxidation is 200-300° C., and the time is 1-3 h; the temperature of the carbonization is 800-900° C., and the time is 1-3 h, and the carbonization atmosphere is nitrogen; The mass ratio of the molybdenum source, the sulfur source and the quaternary ammonium salt is 1:2-4:0.01-0.05; the temperature of the hydrothermal reaction is 180-250° C., and the time is 24-48 hours.
4. The electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material according to claim 1, characterized in that: The polyurethane liquid resin includes one or more of a thermosetting polyurethane resin, an aromatic polyurethane resin, an aqueous polyurethane resin and an aliphatic polyurethane resin; The silane coupling agent includes one or more of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane; The leveling agent includes one or more of an organic silicon leveling agent, a polyether leveling agent and a fluoride leveling agent; The thickener includes one or more of carboxymethyl cellulose, polyurethane thickener, polyacrylate thickener and xanthan gum; The viscosity of the electromagnetic wave absorbing paint is 500-1500 mPa s.
5. The electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material according to claim 1, characterized in that: The components of the electromagnetic wave absorbing coating also include 0.2 to 10% of functional additives; the functional additives include one or more of high temperature resistant additives and antioxidants; the high temperature resistant additives are inorganic aluminum-containing compounds; the antioxidants include one or more of phenolic antioxidants and phosphite antioxidants.
6. The method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing the components to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
7. An electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material, characterized in that: It is formed by the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material according to any one of claims 1 to 5.
8. The method for preparing the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material according to claim 7, characterized in that: The following steps are involved: The electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material is coated on the surface of the substrate and then cured to obtain the electromagnetic wave absorbing coating based on the carbon fiber-molybdenum disulfide composite material.
9. The preparation method according to claim 8, characterized in that: The coating speed is 10-100 cm / min; the coating thickness is 1.5-2.0 mm; the substrate is a flexible substrate; the curing temperature is 60-85° C., and the curing time is 2-4 hours.
10. Use of the electromagnetic wave absorbing coating based on carbon fiber-molybdenum disulfide composite material according to claim 7 in the field of electromagnetic wave absorption.
Citation Information
Patent Citations
Preparation method of graphene-like MoS2 / graphene combined electrode of lithium ion battery
CN102683647A
Ferroferric oxide / molybdenum disulfide / carbon fiber composite wave-absorbing material and two-step reaction preparation method thereof
CN107761364A
Preparation method of spraying electromagnetic wave-absorbing protective fabric
CN114411411A
Fine carbon fiber-containing aqueous polyurethane resin solution and conductive film using the same
JP2015120837A